Cardiopulmonary and analgesic effects of caudal epidurally administered ropivacaine in cattle - Araujo, Marcelo A. [UNESP]; Albuquerque, Veronica B. [UNESP]; Deschk, Mauricio [UNESP]; Santos, Guilherme G. F. [UNESP]; Rodrigues, Celso A. [UNESP]; Oliva, Valeria Nobre Leal de Souza [UNESP]; Santos, Paulo S. P. [UNESP] (Wiley-Blackwell, 2012)
Objective To assess cardiopulmonary and analgesic effects after administration of ropivacaine into the caudal epidural space of cattle.Study design Prospective, single-dose trial.Animals Eight healthy mixed breed cows aged 8 +/- 5 years and weighing 507 +/- 112 kg.Methods Caudal epidural anesthesia was produced in cows with 0.75% ropivacaine (0.11 mg kg(-1)). Onset time, duration and cranial spread of analgesia were recorded. Heart rate (HR), respiratory rate (f(R)), rectal temperature (RT), and mean arterial blood pressure (MAP) were measured prior to epidural administration (T-0) and at 15, 30, 60, 120, 180 and 240 minutes after epidural administration (T-15, T-30, T-60, T-120, T-180 and T-240). Arterial blood acid-base balance (pH, standard bicarbonate and base excess), gas tension (PaO2, PaCO2, SaO(2)) and electrolytes (Na+, K+, iCa(2+), Cl-) were recorded at T-0, T-30, T-60, T-120, T-180 and T-240. Ataxia was evaluated at T-0, T-30, T-60, T-120, T-180 and T-240 and at 1 hour intervals thereafter until analgesia was no longer present in each animal.Results Epidurally administered ropivacaine induced variable analgesia extending bilaterally from the coccyx to S3. Time to onset of analgesia and mean duration in the perineal area were 15 +/- 4 and 359 +/- 90 minutes, respectively. Respiratory rate and RT increased from T-120 to T-240 when compared to the value at T-0. Ionized calcium and chloride concentrations increased at T-180 and T-240 when compared to T-0. The other variables were not significantly different from baseline values (p > 0.05). Four animals were mildly ataxic.Conclusion and clinical relevance Ropivacaine (0.75%, 0.11 mg kg(-1)) can be administered by caudal epidural injection to produce prolonged bilateral perineal analgesia with minimal ataxia and cardiopulmonary changes in standing cattle.
Keywords: blood gas; bovines; epidural; local anesthetics; ropivacaine